Structural Snapshots for Mechanism‐Based Inactivation of a Glycoside Hydrolase by Cyclopropyl Carbasugars. (26th October 2016) - Adamson, Christopher; Pengelly, Robert J.; Shamsi Kazem Abadi, Saeideh; Chakladar, Saswati; Draper, Jason; Britton, Robert; Gloster, Tracey M.; Bennet, Andrew J.
Abstract: Glycoside hydrolases (GHs) have attracted considerable attention as targets for therapeutic agents, and thus mechanism‐based inhibitors are of great interest. We report the first structural analysis of a carbocyclic mechanism‐based GH inactivator, the results of which show that the two Michaelis complexes are in 2 H3 conformations. We also report the synthesis and reactivity of a fluorinated analogue and the structure of its covalently linked intermediate (flattened 2 H3 half‐chair). We conclude that these inactivator reactions mainly involve motion of the pseudo‐anomeric carbon atom, knowledge that should stimulate the design of new transition‐state analogues for use as chemical biology tools.